A time-varying indicator of effective monetary policy conservatism - Michael Berlemann; Kai Hielscher (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2011)
Based on an extended version of a time-inconsistency model of monetary policy we show that the degree of effective monetary policy conservatism can be uncovered by studying to what extent central banks react to real disturbances. By estimating central bank reaction functions in moving and overlapping intervals for the period of 1985 to 2007 using an ordered logit approach in a panel setting we derive a time-varying indicator of effective monetary policy conservatism for Canada, Sweden, the UK and the US. Employing this indicator we show that increasing effective conservatism tends to lower inflation without increasing the output gap. However, while a higher degree of effective conservatism does not result in lower inflation uncertainty the variance of the output gap tends to decrease.
urn:nbn:de:gbv:705-opus-29357
Keywords: E31; E58; 330; central banking; monetary policy; conservatism; central bank independence; inflation